Efficient, flexible and mechanically robust perovskite solar cells on inverted nanocone plastic substrates. Issue 7 (3rd February 2016) - Tavakoli, Mohammad Mahdi; Lin, Qingfeng; Leung, Siu-Fung; Lui, Ga Ching; Lu, Hao; Li, Liang; Xiang, Bin; Fan, Zhiyong
Abstract : Utilization of nanostructures on photovoltaic devices can significantly improve the device energy conversion efficiency by enhancing the device light harvesting capability as well as carrier collection efficiency. Abstract : Utilization of nanostructures on photovoltaic devices can significantly improve the device energy conversion efficiency by enhancing the device light harvesting capability as well as carrier collection efficiency. However, improvements in device mechanical robustness and reliability, particularly for flexible devices, have rarely been reported with in-depth understanding. In this work, we fabricated efficient, flexible and mechanically robust organometallic perovskite solar cells on plastic substrates with inverted nanocone (i-cone) structures. Compared with the reference cell that was fabricated on a flat substrate, it was shown that the device power conversion efficiency could be improved by 37%, and reached up to 11.29% on i-cone substrates. More interestingly, it was discovered that the performance of an i-cone device remained more than 90% of the initial value even after 200 mechanical bending cycles, which is remarkably better than for the flat reference device, which degraded down to only 60% in the same test. Our experiments, coupled with mechanical simulation, demonstrated that a nanostructured template can greatly help in relaxing stress and strain upon device bending, which suppresses crack nucleation in different layers of a perovskite solar cell. This essentially leads to much improved device reliability and robustness and will have significant impact on practical applications.